2013
DOI: 10.1016/j.compfluid.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric lattice Boltzmann model for shallow water flows

Abstract: To cite this version:B. Chopard, P Van Thang, Laurent Lefevre. Asymmetric lattice Boltzmann model for shallow water flows. Computers and Fluids, Elsevier, 2013, 88, pp.225-231. 10.1016/j.compfluid.2013 AbstractWe consider a Galilean transformation of the lattice Boltzmann model for shallow water flows. In this new reference frame, the velocity lattice is asymmetrical but it is possible to simulate flows with Froude number larger than 1 and to model the transition from a torrential to a fluvial regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 14 publications
1
63
0
Order By: Relevance
“…They proposed a set of stability criteria defined based on lattice speed and showed that the scheme remains stable for F = 1 provided that the stability criteria were met. Immediately following their work, Chopard et al (2013) proposed a new 1D shallow water lattice Boltzmann scheme that could be applied to a limited range of supercritical flow regimes. Chopard et al (2013) proposed applying a Galilean transformation to the standard scheme in order to resolve the stability problem in supercritical flow.…”
Section: Limitations For Supercritical Flow Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…They proposed a set of stability criteria defined based on lattice speed and showed that the scheme remains stable for F = 1 provided that the stability criteria were met. Immediately following their work, Chopard et al (2013) proposed a new 1D shallow water lattice Boltzmann scheme that could be applied to a limited range of supercritical flow regimes. Chopard et al (2013) proposed applying a Galilean transformation to the standard scheme in order to resolve the stability problem in supercritical flow.…”
Section: Limitations For Supercritical Flow Modellingmentioning
confidence: 99%
“…Immediately following their work, Chopard et al (2013) proposed a new 1D shallow water lattice Boltzmann scheme that could be applied to a limited range of supercritical flow regimes. Chopard et al (2013) proposed applying a Galilean transformation to the standard scheme in order to resolve the stability problem in supercritical flow. In the new reference frame, moving at a constant speed, the lattice velocity vectors were asymmetric and therefore a new set of equilibrium functions were proposed to account for the moving reference frame.…”
Section: Limitations For Supercritical Flow Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In NSW-LBMs, depth-averaging yields a modified collision operator for subcritical [32] and supercritical [33] flows. Depth-averaged LBM was successfully applied to a variety of illustrative benchmark problems, including wave run-up on a sloping beach [34], applications featuring bed slope and friction terms [35], wind-and density-driven circulation over irregular bathymetry [36] and tank sloshing examples [37].…”
Section: Wave Propagation In Shallow Watersmentioning
confidence: 99%